Isotope effects in dynamics of water isotopologues induced by core ionization at an x-ray free-electron laser - R. Guillemin; L. Inhester; M. Ilchen; T. Mazza; R. Boll; Th. Weber; S. Eckart; P. Grychtol; N. Rennhack; T. Marchenko; N. Velasquez; O. Travnikova; et al. (Structural Dynamics, 2023)
Dynamical response of water exposed to x-rays is of utmost importance in a wealth of science areas. We exposed isolated water isotopologues to short x-ray pulses from a free-electron laser and detected momenta of all produced ions in coincidence. By combining experimental results and theoretical modeling, we identify significant structural dynamics with characteristic isotope effects in H2O2+, D2O2+, and HDO2+, such as asymmetric bond elongation and bond-angle opening, leading to two-body or three-body fragmentation on a timescale of a few femtoseconds. A method to disentangle the sequences of events taking place upon the consecutive absorption of two x-ray photons is described. The obtained deep look into structural properties and dynamics of dissociating water isotopologues provides essential insights into the underlying mechanisms.